(3QSGdI aj CeQ GdfaS hGdeYGOs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3CWGd Gddg HbGA GdTjN GdaGVd dYd SGFd eG bdJg ai GdLhGH GdChd JCedkG HGdESJbUGA ade CSJbd HPdc hJCedJ eG GdSHH GdPi YQV dg s
(3BNQgG (B:s
(3Ch jYOe HYO GdhLhO aEf gPG HGeYfi GdChd jefY ajg HYV GdGTjGA Cf jchf EPG hLOJ jecf Cf ef PGJgG hdjS cd eG djS hLhOg ef PGJg jLhR Cf jRhd hLhOg hgh GdPi djS ajg GdJQcjH GdePchQ hGdMeO dhGgH GdYbd JeJ GdQSGdI s
(3HgG fXGe GdJYbjHIs
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
Keywords: (3GdadSaI hGdefWbs